Chemical and Physical Mechanisms of Fungal Bioweathering of Rock Phosphate. Issue 5 (3rd May 2021) - Mendes, Gilberto de Oliveira; Bahri-Esfahani, Jaleh; Csetenyi, Laszlo; Hillier, Stephen; George, Timothy S.; Gadd, Geoffrey Michael
Abstract: This research has investigated fungal transformations of rock phosphate (RP) by geoactive fungi, with particular emphasis on Aspergillus niger . Direct hyphal interaction with RP particles induced morphological and mineralogical changes, as revealed by scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis. The formation of the oxalate mineral calcium oxalate monohydrate (whewellite, CaC2 O4 ·H2 O) on RP surfaces showed that mycogenic oxalic acid was driving the chemical dissolution of apatite, with consequent phosphate release and secondary mineral formation. This was supported by abiotic testing of common fungal excreted organic acids which confirmed that oxalic acid was the only effective RP transforming agent and therefore responsible for the morphological and mineralogical changes observed in RP when exposed to fungal colonization. Cryogenic SEM provided evidence of fungal penetration and tunneling through RP particles demonstrating that physical interactions are also important for RP bioweathering, as well as biochemical mechanisms. These findings emphasize the important role of fungi in P cycling, with active participation in the transformation of mineral phosphates through physicochemical mechanisms and secondary oxalate biomineral formation.